The Role of International Academic Professionals in the Development of Entrepreneurial Universities in South Africa: Government Funded Universities Perspective - Mutanda, Mary; Lekhanya, Lawrence Mpele; Moyo, Sibusiso (Journal of Economics and Behavioral Studies, 2018)
There is a wide belief and acceptance from leading government and business experts that small enterprises and entrepreneurship are the key components to unemployment and poverty alleviation in any country. Unfortunately, high unemployment levels, low entrepreneurial activity and high small business failure rate have become the main characteristics of the South African economy. Post-school education is partially blamed for the dropping levels of entrepreneurial activities in the country. South Africa’s tertiary education system continues to focus on producing job-seekers instead of job creators. This problem has forced South African Universities to explore more on their potential of becoming more entrepreneurial, but lack of academics in the field of entrepreneurship has been found to be a hindrance to success in this agenda. To avert this obstacle, it is reiterated that internationalisation is key to any university entrepreneurship strategy, and therefore universities are encouraged to internationalise through attracting international entrepreneurial staff. The purpose of this literature review paper is twofold. The first part explores the role played by international academic professionals in the establishment of entrepreneurial universities in South Africa, while the second aims at evaluating the state of entrepreneurship development in higher education and the potential of South African universities becoming more entrepreneurial. The study employs both quantitative and qualitative research techniques (mixed method). The study reveals that South African universities should internationalise if they are to succeed in the entrepreneurial strategy. In addition, it is found that foreign academics have the required skills and bring in the diverse expertise needed for the establishment of entrepreneurial universities. Moreover, the presence of international academics has enhanced entrepreneurship mindset of local staff and students. It is recommended that universities should establish entrepreneurial institutes which are affiliated to them in order to drive this initiative and that the establishment of entrepreneurial universities is the way to go in South Africa if the country is to beat poverty and unemployment.